PERAN PENDIDIKAN KEWIRAUSAHAAN SEKOLAH DALAMM MEMBANGUN GENERASI STAR UP : KAJIAN LITERATUR SISTEMATIS - M. Alwi Abdul Aziz; Fahriz Rizaldi Alqosimi; Rina Rosiana; Chindi Ramadani; Idham Kholid (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of the digital economy demands that the world of education produce a young generation that is not only academicall proficient, but also possesses a creative and innovative entrepreneurial spirit. However, reality shows that the implementation of entrepreneurship education in schools still faces challenges such as limited facilities, a lack of teacher competence, and minimal collaboration with the industrial world. This study aims to analyze the role of entrepreneurship education in schools in developing a sturtup generation through a Systematic Literature Review (SLR) approach. Date were collected from various relevant national and international journals from 2015-2025, then analyzed using thematic synthesis methods to identify patterns, strategies, and key findings. The result show that enterpreneursip education in schools contributes significantly to improving student’s creative thinking skills, problem solving skills, and innovation abilities. Project based learning models and digital entrepreneurship have proven more effective in developing entrepreneurial character that adapts to digital transformation. Teachers play a crucial role as visionary facilitators in fostering an entrepreneurial spirit through contextual and collaborative learning. That study’s conclusions emphasize that strengthening teacher capacity, providing supporting facilities, and partnering with industry are key to the success of entrepreneurship education in schools. The implications of this research emphasize the need to integrate a digital based entrepreneurial ecosystem in schools to produce a generation of innovative and globally competitive startups.